2014
DOI: 10.1039/c3cp54280g
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced electron transfer of zinc porphyrin–oligo(thienylenevinylene)–fullerene[60] triads; thienylenevinylenes as efficient molecular wires

Abstract: Two novel donor-bridge-acceptor arrays (ZnP-nTV-C60) with zinc porphyrin (ZnP) and fullerene (C60), covalently connected by oligo(thienylenevinylene) (nTV) molecular wires (n = 3 and 8; ), have been prepared in a multistep convergent manner. The influence of the nTV-length on the electrochemical and electronic properties of the ZnP-nTV-C60 triads has been revealed. Interestingly, an efficient photoinduced electron transfer process occurs in both triads with formation of intermediate radical-ion pairs (namely, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…The values of first oxidation (E ox ) and first reduction potential (E red ) of 1, 2 and PC 70 BM have been listed in Table 3. The free-energies for charge-separation (DG CS ) obtained from the singlet excited state of diporphyrins, namely, 1 and 2, and free energies of charge-recombination (DG CR ) of the excited singlet state have been enumerated using spectroscopic and electrochemistry data according to the approach of Rehm and Weller [35] and Ito et al [16] and the values of various important physicochemical parameters including singlet excited energy state (E 0-0 ), static energy (DG S ) and radical ion-pair potential energy (E RIP ) are given in Table 1. We have also estimated free-energy of electron transfer (DG 0 ) for the complexation between PC 70 BM and diporphyrin in dichloromethane.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of first oxidation (E ox ) and first reduction potential (E red ) of 1, 2 and PC 70 BM have been listed in Table 3. The free-energies for charge-separation (DG CS ) obtained from the singlet excited state of diporphyrins, namely, 1 and 2, and free energies of charge-recombination (DG CR ) of the excited singlet state have been enumerated using spectroscopic and electrochemistry data according to the approach of Rehm and Weller [35] and Ito et al [16] and the values of various important physicochemical parameters including singlet excited energy state (E 0-0 ), static energy (DG S ) and radical ion-pair potential energy (E RIP ) are given in Table 1. We have also estimated free-energy of electron transfer (DG 0 ) for the complexation between PC 70 BM and diporphyrin in dichloromethane.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…Supramolecular donor-acceptor hybrids consisting fullerene and porphyrin finds potential application in sensing, switching and catalysis other than electron transfer [15]. El-Khouly et al have observed that an efficient photoinduced electron transfer process occurs in case of zinc porphyrin-oligo (thienylenevinylene)/fullerene[60] triads [16]. Very recently, Ito and D'Souza et al have shown facile electron transfer for fullerene/zincporphyrin supramolecular dyads [17] in dichloromethane.…”
Section: Introductionmentioning
confidence: 98%
“…p-Conjugated oligomers as oligothiophene (OT) [5] and oligophenylenevinylene (OPV) [6] moieties have been shown to act as long distance molecular wires in the efficient photoinduced electron transfer from the porphyrin chromophore to the fullerene. Recently, we have described the use of oligothienylenevinylene oligomers (nTVs) [7], where the thiophene moieties was substituted by alkyl chains, as efficient bridges in donor-donor [8], acceptoracceptor [9] or donor-acceptor [10] systems showing an attenuation factor for electron transfer as low as 0.016 Å -1 [11]. The functionalization of thiophenes with ethylenedioxy groups produced the well known 3,4-ethylenedioxythiophene (EDOT).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with DSSCs, it has taken quite a while for porphyrins to demonstrate their potential in BHJ solar cells. However, they have been widely studied for their good ability to photo‐transfer electrons to C 60 derivatives . Thus, ultra‐fast electron transfer, and charge Separated (CS) states of several nanoseconds have been observed .…”
Section: Introductionmentioning
confidence: 99%